SAND CASTING MANUFACTURER WITH MATERIAL ADDITIVE TO PERMEABILITY AND GREEN COMPRESSIVE STRENGTH CHARACTERISTIC - Yusup Hendronursito; Muhammad Amin; Kusno Isnugroho; David Candra Birawidha (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2019)
Sand casting as a main material in the casting process. To result from the product in good quality sand casting must be standardized such as high-temperature resistance, good permeability to gas flow, high strength to enough to hold the loading press, and high shear strength to accept shear force. This study to aims effect of material added on green sand as sand casting to find the best composition on permeability, green compressive strength, and green shear strength. Glass powder in sample A and feldspar in sample B used to material binder selected an alternative beside bentonite because have high Silica (SiO) and Alumina (Al2O3) to optimizing the sand casting characteristic. The binder material meshing in < 80 Mesh with 10%, 20%, 30%, 40%, and 50% composition respectively with 10% constant addition of water. Every sample three times testing included clay content, Grain Fine Number based on SNI 19-0312-1989 while permeability, green compressive strength, and green shear strength. The result shows the permeability directly proportional with glass powder addition has a maximum of 63.67, while the addition of feldspar affected decrease the permeability value with a minimum of 51.67. The higher green compressive strength obtained from 10% w/t glass powder with value 96.87 kN/m2 inversely proportional with green shear strength with value 76.27 kN/m2 in 10% w/t addition.